PHYSICAL FITNESS SURVEY OF BANYUMAS KARESIDENAN BASKETBALL REFEREES - Pratama, Raditya; Ruman (EDUCATUM: Scientific Journal of Education, 2023)
The results of preliminary data observations of referees who have never conducted a physical fitness test (TKJI) at PERBASI Banyumas since 2015 until now. Based on the results of observations, it is important to conduct physical fitness research with the title "Physical Fitness Survey of Banyumas Karesidenan Basketball Referees". The aim is to find out how much the level of physical fitness of basketball referees from licenses C, B2, B1 and A in Perbasi Karesidenan Banyumas. The method is a survey. The sample taken was a total of 25 referees, consisting of 22 male referees and 3 female referees. The measurement technique of the test form is the TKJI version of the physical fitness test. The data collected was analyzed using quantitative descriptive statistical techniques. Based on the results of the percentage count there are 1 referee or 4% have physical fitness in the good category, then there are 2 referees or 8% have physical fitness in the moderate category, then there are 6 referees or 24% have physical fitness in the less category and there are 16 referees or 64% have physical fitness in the very less category. Based on the results of the data research above, it can be concluded that the level of physical fitness of the basketball referees of PERBASI Banyumas Karesidenan as a whole is dominant in the Less category.